Greenland, view of Kjerulf Fjord annotated by Louise A. Boyd - Boyd, Louise Arner, 1887-1972 (1931)
August 1, 1931. Kjerulfs [Kjerulf] Fjord. Extreme inner end of Main Valley. Mountain range forming the eastern side of Kjerulfs [Kjerulf] Fjord; from their entrance at Kaiser Franz Josef Fjord [Kejser Franz Joseph Fjord] these mountains continue Main Valley, then curve through Left Valleys and, reaching their southern terminal, curve to the left (E.N.E.) and become north side of Dickson [Dicksons] Fjord.